PENGGUNAAN PUZZLE JAM DALAM MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 5-6 TAHUN DI PAUD AISYIYAH 1 KECAMATAN SENAPELAN KOTA PEKANBARU - Normis Normis; Zulkifli N Zulkifli N; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to improve the children's ability to recognize the concept of numbers through a puzzle hours in early childhood Aisyiyah 1 Senapelan District pekanbarucity. This research is a class act who performed two cycles. Each cycle held 3 meetings. Sabjek this study was children in group B numbering 15 children. The object under study is the ability to recognize the concept of numbers through a puzzle hours. Data collection methods used were observation. Data were analyzed using quantitative. The results showed an increased ability to recognize the concept of the number of children in group B through the puzzle hours at a time before action is taken the percentage of children's ability to recognize the concept of number is 37.7% with the criteria undeveloped (BB) and after implemented measures the ability to know the concept of child number increased to 76.77 with a very well developed criteria (BSB).Keywords: The ability to recognize the concept of numbers, puzzle hours, children in group B